Menjelajahi Kesehatan Fisik Dan Mental Di Era Gen Z - Sri Panny Rahmasari; Darmeinis Darmeinis; Nagiyah Putri; Dwi Hana Talitha; Diana Nur Islamiyah; Baitul Rohim; Rezka Dimas Prasetyo; Wiwi Hera Wati; Fikrih Hardiansah (FKIP, Universitas Palangka Raya, 2024)
Generation Z, born approximately between 1997 and 2012, grew up in a period characterized by advancements in digital technology, globalization, and unique social pressures. This article explores the dynamics of physical and mental health among Gen Z, focusing on the challenges and opportunities they face. Physically, a sedentary lifestyle driven by reliance on technology and changes in modern dietary patterns has increased the risk of obesity and metabolic disorders. On the other hand, growing awareness of the importance of exercise and healthy living paves the way for improvement. In the context of mental health, Gen Z experiences higher levels of anxiety, depression, and stress compared to previous generations, largely due to academic pressures, social expectations, and intense exposure to social media. However, the stigma surrounding mental health is gradually diminishing, with more individuals seeking professional help. This article also highlights the importance of a holistic approach, including the integration of digital health technologies and community-based programs, in supporting the well-being of this generation. With a deeper understanding, cross-sector efforts can be made to create an environment that better supports the physical and mental health of Gen Z.